2009
DOI: 10.1039/b909587j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural characterization and in vitro cytotoxicity of new Au(III) and Au(I) complexes with thioamides

Abstract: The reactions of tetrachloroauric(III) acid (HAuCl4) with the thioamides; 2-mercapto-benzothiazole (mbztH) and 5-ethoxy-2-mercapto-benzimidazole (EtmbzimH) lead to the desulfuration of the ligands and the formation of the ionic complexes {[AuCl4]- [bztH2]+} (1), and {[AuCl4]- [EtbzimH2]+ (H2O)} (2) (where bztH2+ and EtbzimH2+ are the desulfurated cations of the starting ligands). The reaction of HAuCl4 with 2-mercapto-nicotinic acid (mnaH2), however results in the formation of 2-sulfonate-nicotininc acid (C6H5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 33 publications
2
33
0
2
Order By: Relevance
“…Au(III) is very short-lived in the presence of different biomolecules because it can rapidly oxidize them, thereby being reduced to Au(I). It has been known for some time that Au(III) can oxidize thiols to disulfides [28,29], cleave the disulfide bond of cystine to give the sulfonic acid [28][29][30][31], oxidize dialkyl sulfides to sulfoxide [32], the sulfur atom of the amino acid methionine stereospecifically to methioninesulfoxide [33][34][35][36][37], and can desulfonate thioamides [38]. The structural consequences of these reactions can play an important role in the toxic side effects of gold-based drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Au(III) is very short-lived in the presence of different biomolecules because it can rapidly oxidize them, thereby being reduced to Au(I). It has been known for some time that Au(III) can oxidize thiols to disulfides [28,29], cleave the disulfide bond of cystine to give the sulfonic acid [28][29][30][31], oxidize dialkyl sulfides to sulfoxide [32], the sulfur atom of the amino acid methionine stereospecifically to methioninesulfoxide [33][34][35][36][37], and can desulfonate thioamides [38]. The structural consequences of these reactions can play an important role in the toxic side effects of gold-based drugs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the IC 50 value for PC3 cancer cells of complexes showed that the complexe (1) is relatively more effective cytotoxic agent than complexes (2) and (3) which is comparable to cisplatin [52]. Gold complexes have recently gained significant attention as a class of compounds with different pharmacodynamic and kinetic properties than cisplatin with strong cell growth inhibiting effects [53,54]. The cell growth inhibiting effects, in many cases, could be related to anti-mitochondrial effects that make the gold complexes interesting [53,55,56].…”
Section: Cytotoxic Assay Pc3 Cellsmentioning
confidence: 99%
“…Gold complexes have recently gained significant attention as a class of compounds with different pharmacodynamic and kinetic properties than cisplatin with strong cell growth inhibiting effects [53,54]. The cell growth inhibiting effects, in many cases, could be related to anti-mitochondrial effects that make the gold complexes interesting [53,55,56]. However, the NPs can be incorporated with dual targets, the androgen receptor (AR1) which is a target for prostatic cancer therapy and a G protein receptor (GRC6A), which is seen upregulated in cancer prostate.…”
Section: Cytotoxic Assay Pc3 Cellsmentioning
confidence: 99%
“…Gold thiolates are used clinically against rheumatoid arthritis 1 . Auronofin (triethylphosphine-gold(I) thioglugose (Et3PAuTg)) and its second generation drug Ridaura TM (triethylphosphine(2,3,4,6-tetra-acetyl-glycopyrasonato-S-)gold(I)), an extensively gold(I) anti-arthritic drug in use, were found to be highly cytostatic to tumour cells and active against i.p.…”
Section: Introductionmentioning
confidence: 99%